2021
DOI: 10.1097/scs.0000000000007584
|View full text |Cite
|
Sign up to set email alerts
|

Skating on Thin Ice: Craniofacial Injuries in Amateur Ice Hockey

Abstract: bleeding profusely and probably contaminated, we recommend contacting emergency services. If a laceration is not suspected, the layperson should next move on to determining whether the injury is a concussion or contusion. If only bruising is seen, and the player exhibits no significant accompanying symptoms, then the player and layperson may decide together whether to continue playing. If there are more severe symptoms such as confusion, headache, lack of coordination, or blurry vision, concussion should be su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Most patients were not severely injured, with a median ISS of 4 [4][5][6][7][8][9] (Table 2). The lower extremities were the most commonly injured body region (29%), followed by the head, upper extremities, and abdomen (19%, 17%, and 15% respectively).…”
Section: Patient Demographics Clinical Data and Injury Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Most patients were not severely injured, with a median ISS of 4 [4][5][6][7][8][9] (Table 2). The lower extremities were the most commonly injured body region (29%), followed by the head, upper extremities, and abdomen (19%, 17%, and 15% respectively).…”
Section: Patient Demographics Clinical Data and Injury Datamentioning
confidence: 99%
“…1 Despite this enthusiasm and relatively robust literature on the sport in many ways, national-level analyses of patient demographics, clinical characteristics, and injury data are lacking. In hockey and other contact sports, attention has recently been given to injury prevention, especially in terms of head, 2,3 face, [4][5][6][7] and mouth [8][9][10] injuries. Helmets, visors, and mouthguards are frequently required to play hockey, as injuries can be sustained via a number of different mechanisms including falling on the ice or into the boards, puck strike, or contact with another player.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have found that the head and neck (HN) is the most common site of surfing injury treated within health care facilities, comprising 45% to 51% of injuries overall 4,10. Given the rising popularity of the surfing, there is a need for detailed craniofacial injury data of the same quality of studies previously published for other sports including ice hockey, golf, volleyball, tennis, and contact sports 11–15. Therefore, we undertook an analysis of the National Electronic Injury Surveillance System (NEISS) database to further elucidate the characteristics of surfing-related craniofacial trauma presenting to the ED.…”
mentioning
confidence: 99%
“…4,10 Given the rising popularity of the surfing, there is a need for detailed craniofacial injury data of the same quality of studies previously published for other sports including ice hockey, golf, volleyball, tennis, and contact sports. [11][12][13][14][15] Therefore, we undertook an analysis of the National Electronic Injury Surveillance System (NEISS) database to further elucidate the characteristics of surfing-related craniofacial trauma presenting to the ED. Our objective is to quantify these data to both help ED providers provide high quality care, and to help inform possible measures of injury prevention in the future.…”
mentioning
confidence: 99%